Clinical Characteristics of Cognitive Impairment and 1-Year Outcome in Patients With Anti-LGI1 Antibody Encephalitis - Hang, Hai-lun; Zhang, Ji-hong; Chen, Dao-wen; Lu, Jie; Shi, Jing-ping (Frontiers in Neurology, 2020)
Introduction: Anti-leucine-rich glioma-inactivated 1 antibody (anti-LGI1) encephalitis is one of the most common autoimmune encephalitis. Anti-LGI1 encephalitis presented with subacute or acute onset of cognitive impairment, psychiatric disturbances, faciobrachial dystonic seizures (FBDSs), convulsions, and hyponatremia. The common sequela of anti-LGI1 encephalitis is cognitive disorder, but there are few studies on the recovery of cognitive function after immunotherapy. This study aimed to explore clinical characteristics of cognitive impairment and 1-year outcome in patients with anti-LGI1 encephalitis. Methods: The clinical data and characteristics of cognitive impairment of 21 patients with anti-LGI1 encephalitis from 2016 to 2019 in Nanjing Brain Hospital were analyzed retrospectively. At the time of onset of hospitalization and 1 year after discharge, the cognitive functions in these patients were assessed using two cognitive screening scales—Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment-Basic (MoCA-B). Results: Among the 21 patients, 13 were male and 8 were female, aged 51.10 ± 14.69 (age range 20–72) years. Nineteen patients, comprising 90.48%, had recent memory deterioration. Routine electroencephalography (EEG) results of 13 cases were abnormal. EEG results were epileptic or slow-wave activity involving the temporal lobes. Eleven cases of brain MRI were abnormal, and the focus involved the hippocampus and mediotemporal lobe. The decrease of short-term memory [recall scores: 0.57 ± 0.81 (MMSE), 0.76 ± 1.34 (MoCA-B)] is the most obvious at the time of admission. After intravenous (IV) injection of methylprednisolone and/or immunoglobulin, the clinical symptoms of the patients improved obviously. Total MMSE and MoCA-B scores of patients were significant increased after 1 year (21.19 ± 3.54 vs. 26.10 ± 3.02, P < 0.001; and 19.00 ± 4.38 vs. 25.19 ± 4.25, P < 0.001, respectively). Recall scores and orientation scores of MoCA-B were significantly improved after 1 year (0.76 ± 1.34 vs. 3.24 ± 1.48, P < 0.001; and 3.10 ± 1.26 vs. 5.00 ± 1.22, P < 0.001, respectively). However, 3/21 (14.29%) patients still have obvious short-term memory impairment (recall scores ≤ 1). Conclusion: Cognitive impairment is one of the most common manifestations of anti-LGI1 encephalitis, with the main prominent being acute or subacute short-term memory loss. Although most patients with anti-LGI1 encephalitis respond well to immunotherapy, a small number of patients still have cognitive disorders, mainly recent memory impairment, after 1 year.